Antioxidant Supply and Its Effect On Concentration Of Collagen In National League Weightlifters’ Blood - Ali, Hussein; Khalid, Omar (Journal of Physical Education, 2018)
Antioxidant Supply and Its Effect On Concentration Of Collagen In National League Weightlifters’ Blood The aim of the research is to design a program for the supply of Antioxidant Ultimate Nutrition which contains vitamin C, A, , E, Z, Glutathione (GSH), Selenium as well as identifying collagen concentration ratio in the blood of weightlifters. The researcher used the experimental method. The subjects were national league weightlifters. The experiment lasted for two months. The data was collected and treated using (SPSS). The researcher concluded that the supply of antioxidants had a significant effect on the collagen index in pre and posttests (before and after effort). The researcher recommended making regular blood tests for athletes to monitor the change in biochemical indicators and for the health of athletes. The researcher recommended providing supply of antioxidants to athletes in various activities before and after training to upgrade the level of athlete in terms of biochemical indicators and increasing the period of the experiment to obtain better development in the research variables, especially with samples of high level.